QAS 2023
DOI: 10.47750/qas/24.194.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between High-Performance Work Practices (Hpwps) And Achieving Organizational Excellence

Abstract: Since high-performance work practices (HPWPs) are thought to have an effect on organizational excellence, experts argued on the unique process through which HPWS influence leads to organizational excellence. The aim of this study to examined the relationship between high-performance work practices and achieving organizational excellence. This study collected the data from 155 senior managers across 15 different enterprises operating within the engineering, electronics, and information technology (EEIT) sectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…[23] confirms the importance of the firm effect on sustainable organizational performance, regardless the firm size. On top of that, the research of [24] underlines "the need of a long-term plan for reaching the organizations aim" of sustainability.…”
Section: B Fundamential Notion Research Trends and Scientificmentioning
confidence: 99%
“…[23] confirms the importance of the firm effect on sustainable organizational performance, regardless the firm size. On top of that, the research of [24] underlines "the need of a long-term plan for reaching the organizations aim" of sustainability.…”
Section: B Fundamential Notion Research Trends and Scientificmentioning
confidence: 99%
“…High-performance work practices (HPWPs) are a component of the organisational strategy to address the employment agreement (Manresa et al, 2021;Ogbonnaya & Valizade, 2018). Through a unique fusion of activities, HPWPs seek to increase employee productivity by enhancing their knowledge, inspiration, engagement, cooperation, flexibility, and involvement (Mansour et al, 2023). The three characteristics of HPWPs that impact organisational excellence are: increasing worker knowledge, skills, and capabilities; empowering and involving workers in decision-making and problem-solving processes; and incentivising workers to work harder and more devotedly (Kooij & 27th International Congress on Project Management and Engineering Donostia-San Sebastián, 10th-13th July 2023…”
Section: Achieving Organizational Excellence Through High-performance...mentioning
confidence: 99%
“…Empowering employees and implementing high-performance work practices create an environment conducive to agility. Empowered employees with the necessary skills and resources can better adapt to changing project requirements, overcome challenges, and make informed decisions, thereby positively impacting project success (Mansour et al, 2023;Rhee et al, 2020;Zaman et al, 2022). Previous studies have demonstrated the positive influence of high-performance work practices on project outcomes, including improved project performance, higher-quality deliverables, increased productivity, and better adherence to project timelines and budgets.…”
Section: Answering the Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation